Value creation dynamics in a project alliance. Issue 5 (July 2019) - Pargar, Farzad; Kujala, Jaakko; Aaltonen, Kirsi; Ruutu, Sampsa
Abstract: Project alliance requires all parties to work together in good faith, share project risks, and make unanimous decisions for the betterment of the project. A key feature of successful implementation of a project alliance is a focus on value creation and value for money. This paper proposes a qualitative system dynamics model to specify and explain dynamics of value creation processes in the context of project alliance. By synthesizing the existing literature and reports on project alliancing, this paper identifies four processes that have a strong influence on the value created in the project alliance context: work progression, rework, redesign and innovation, and rescheduling. In addition, we show how these value creation processes are interrelated and evolve over time. The effectiveness of these processes is influenced by the capability and motivation of the project alliance partners to discover works that do not fully utilize the available resources, and make quick decisions to capture these benefits. Highlights: A qualitative system dynamics model is developed to specify and explain value creation dynamics in project alliance context. This paper identifies four processes that have a strong influence on the value creation. The model shows the interrelations among work progression, rework, redesign and innovation, and rescheduling processes. The model explores how alliance practices and culture and project contingency factors influence the value creation processes.